THE EFFECT OF EMPOWERMENT ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS MEDIATING VARIABLE AND ORGANIZATIONAL CULTURE AS MODERATION VARIABLE - Lilik Lestari; Askar Yunianto (Conference In Business, Accounting, And Management (CBAM), 2015)
This study examines the effect of employee empowerment on employee performance with organizational commitment as mediating variables and organizational culture as a moderating variable. This study was based on previous research conducted Fadzilah (2006), Praptadi (2009), Rahman (2009), Tielung (2013), Kambey and Suharnomo (2013), Rahayu and Sudibia (2014), Srinadi and Netra (2014) which states empowerment positive and significant effect on the behavior of employees. This study focused on Lung Hospital dr. Ario Wirawan Salatiga. The method of sampling a total of 210 employees used a simple random sampling. The statistical method used to test the hypothesis of linear regression of moderation and mediation. The results showed that employee empowerment significant indirect effect on employee performance through organizational commitment to be moderated by organizational culture.Key words:Â  Employee Empowerment, Organizational Commitment, Organizational Culture, Employee Performance